Towards a multilingual linguistic competence - María Luisa García Gurrutxaga (ADIDE Federación, 2010)
Since the Common European Framework of Reference for Languages: Learning, Teaching and Assessment was published (Council of Europe, 2001), the awareness of the importance of the development of the multilingual competence of citizens and therefore of students has gradually increased. In the above mentioned document it is also possible to make out a definition of communicative competence that has immediate consequences not only in the different school curricula but also in the decisions that language teachers have to take about the learning/teaching process in their classrooms.